In the Footsteps of Publishing of Motiejus Valančius’ „Vaikų knygelė“ - Maskuliūnienė, Džiuljeta (Acta humanitarica academiae Saulensis, 2023)
1868 was a fateful year for Lithuanian children’s literature, as two books by Samogitian Bishop Motiejaus Valančius (1801–1875) appeared: "Vaikų knygelė" (Engl. Children’s Book) and "Paaugusių žmonių knygelė" (Engl. Adolescence Book). They mark the beginning of literature for Lithuanian children and teenagers. This is evidenced not only by the symbolic titles of both books, which indicate the addressee – children and teenagers, young people. It is important that Valančius thinks about a specific reader – a child, so in the Foreword of the "Vaikų knygelė" he hopes that “children will not regret while reading” his book, that is, they will not get bored. The author thinks that children while reading Aukso altorius (Engl. Golden Altar) only find prayers and litanies, however, they want to learn about interesting things to tell others, and if they do not find such things, “sometimes they can’t even learn”. Therefore, it is necessary to read special books for children in the post-elementary period. It was a modern approach in those times, which is not outdated even today.The article aims to discuss the publishing path of Valančius’ "Vaikų knygelė" as well as the most important modifications (textual and visual) this collection of didactic short stories underwent. The article analyses the following aspects: 1) issues of selection of texts and their presentation; 2) preservation of the dimension of authenticity of texts; 3) what was the presentation of the texts of Valančius’ "Vaikų knygelė" written in dialect over time.It is very important to emphasize that the linguistic expression of Valančius’ works, especially the stylistic layer, is an interesting phenomenon in all Lithuanian literature. Paradoxically, when the reissues were published, the stylistic layer of the works was often affected, the dialect was levelled, so a considerable part of the authentic layer, the exotic whiff of didactic prose of the 19th century, was “erased”. The interdisciplinary research approach is employed in the present research, the perspectives of literary studies, textology and art studies are combined: it is based on the scientific insights of the literary expert and textologist Paulius Subačius, the analysis of the illustrations of various editions of Valančiaus’ "Vaikų knygelė" by the art critic Ingrida Korsakaitė, the considerations of the literary researcher Vanda Zaborskaitė on the aesthetic value of the archaic nature of Valančius’ text, etc.
Keywords: Motiejus Valančius; Vaikų knygelė; lietuvių vaikų literatūra; leidyba; redagavimas; kūrybos autentiškumas; iliustracija